2019
DOI: 10.1055/s-0039-1697562
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Artery Hypoplasia in a Select Adult Kenyan Population

Abstract: Background Hypoplasia of cerebral arteries predisposes to stroke and cerebral aneurysms which have an increased incidence in sub-Saharan Africa. The frequency and pattern of cerebral artery hypoplasia, however, shows population variations, and data from the African population remain scanty. Objectives This study aimed to determine the percentage of hypoplasia in the anterior, middle, and posterior cerebral, anterior and posterior communicating, basilar, and vertebral arteries. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The “Charcot artery of cerebral hemorrhage,” which is a branch of the middle cerebral artery, is the most common artery to bleed. Here, in this study from the Kenyan population, Ogengo et al 4 observed that the middle cerebral artery is least commonly affected with the hypoplasia. This suggests that the middle cerebral artery is prone for hemorrhagic stroke than ischemic.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…The “Charcot artery of cerebral hemorrhage,” which is a branch of the middle cerebral artery, is the most common artery to bleed. Here, in this study from the Kenyan population, Ogengo et al 4 observed that the middle cerebral artery is least commonly affected with the hypoplasia. This suggests that the middle cerebral artery is prone for hemorrhagic stroke than ischemic.…”
mentioning
confidence: 54%
“…In this Kenyan African study, 4 the authors observed that the posterior communicating artery, which connects the carotid and vertebral arterial system, is more prone for hypoplasia. This factor may hinder the effective anastomosis between the major arterial inputs of brain.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…[ 15 ] Besides, BTAs also present a unique anatomic configuration and it is well known that the supply and discharge vessels of the basilar artery are often subject to anatomical asymmetries. [ 7 , 14 , 19 , 21 ] Nowadays, it is unclear to what extent this asymmetry of the vertebral arteries (VAs) and the PCAs affects the local flow dynamics or if it is a risk factor for aneurysm rupture or aneurysm growth in BTAs.…”
Section: Introductionmentioning
confidence: 99%